Biodiesel production from waste cooking oil blend with calophyllum inophyllum through microwave irradiation-assisted transesterification method / Jassinnee Milano - Jassinnee , Milano (2019)
Recycling waste cooking vegetable oils by reclaiming and using these oils as biodiesel feedstocks is one of the promising solutions to address global energy demands. However, producing these biodiesels poses a significant challenge because of their poor physicochemical properties due to the free fatty acid content and impurities present in the feedstock, which will reduce the biodiesel yield. Hence, the following strategy were implemented in order to address this issues: (1) 70 (v/v)% of waste cooking vegetable oil blended with 30 (v/v)% of Calophyllum inophyllum oil to alter its roperties, (2) a three-stage process was carried out (degumming, esterification, and transesterification) which reduces the free fatty acid content and presence of impurities, (3) the transesterification process parameters (methanol/oil ratio, reaction temperature, reaction time, and catalyst concentration) were optimized using response surface methodology by conventional reactor, and (4) optimization study of microwave irradiation-assisted alkaline-catalysed transesterification was used to produce W70CI30 biodiesel and the reaction parameters (methanol/oil ratio, catalyst concentration, stirring speed, and reaction time). It is found that microwave irradiation-assisted transesterification is an effective method to boost the biodiesel yield and superior biodiesel quality. Moreover, this method significantly reduces the total time (preheated and reaction time) of the transesterification process to 9.15 min. and the process is energy-efficient. lending of W70CI30 biodiesel-diesel fuels at ratio of B10, B15, B20, B25 and B30 have shown an increase in viscosity, density, and acid value. However, it was observed that the heating value has decreases gradually when the concentration of the W70CI30 was increased. Even though there is a change in the properties of the blending fuels, but the changes are within the limits of ASTM D6751 and EN 14214 standard method. This indicate that the blended diesel-biodiesel fuels re suitable to be used as fuels for diesel engine. Besides, the biodiesel-lubricant blends and biodiesel-diesellubricant blends were investigated to observe the wear and coefficient of friction of aforementioned blend. The scar wear diameter has shown that as the ratio of biodiesel is increases in the blend, the wear scar diameter decreases gradually. Biodiesel-diesellubricant blend show a much lower scar diameter than the biodiesel-lubricant blends at higher lubricant blend. The corrosion examination on the blended W70CI30 biodiesel-diesel fuels blend was performed on metallic materials such as mild steel and stainless-steel 316. It was observed that the mild steel has started to corrode after it is immersed in the fuel blends. The corrosion rate increases as the time of immersion and the biodiesel-diesel blend ratio increases. For the stainless steel 316 materials, there is no corrosion observed for the initial 2 months immersed period for B5 till B20 but there is a slight corrosion was observed on the B25 and B30 fuel blends at the mentioned period. Besides, the physicochemical properties such as viscosity, density, and reflexive value have significantly shown the degradation of the fuels. Therefore, waste cooking vegetable oil blend with Calophyllum inophyllum are potential feedstocks to replace the diesel and microwave irradiation is an effective equipment to produce high quality biodiesel.